Análisis cefalométrico lateral integrado, según edad y sexo, de pacientes entre los 6 y los 14 años de edad (2003)
ABSTRACT: Standard measurements are applied to all patients in most of the available cephalometrics analysis, even tought There is a great diversity on the measurements due to age and gender. It is important to note that most of the studies in this area have been permormed on adult subjets. Tables included in this article provide linear measurements of various parts of the craniofacial skeleton of boys and girls with ages between 6 and 14. There are also angular measurements that relate some of these parts to others. The object of this research is to facilitate the lateral caphalometric analysis of patientes by making the process more organizad and complete. The process will then allow a more acurate diagnosis with a more appropiate treatment for each patient. Key words: cephalometrics, Analysis, Maxilla, Mandible, Incisors.